Unlocking Potential: A Teacher's Lens on Artificial Intelligence Towards Students' Problem-Solving Skills - Barus, Yohannes Kurniawan; Pangestu, Widya Trio; Muzaki, Ferril Irham; Ahdhianto, Erif (Journal of Integrated Elementary Education, 2025)
The advancement of information technology is opening up new avenues for integrating artificial intelligence into education. However, there is a prevailing belief that the use of AI could impact students' problem-solving abilities. This research seeks to explore teachers' perceptions regarding the potential influence of artificial intelligence on these skills. Utilizing a quantitative approach, the study involved a survey conducted with 57 participants. Data was collected through a questionnaire and subsequently analyzed descriptively. The findings reveal several key insights: (1) teachers generally agree that AI, particularly tools like ChatGPT, can enhance students’ engagement in problem-solving activities, (2) the primary challenge in implementing AI is navigating ethical concerns, and (3) students indeed benefit from the support of AI in problem-solving tasks, especially in the area of formulating solutions. These results underscore the importance of encouraging the integration of AI technologies, such as ChatGPT, into teaching methods in elementary schools. Such integration could foster a more interactive and adaptive development of students' problem-solving skills. Moreover, the positive views held by teachers about using AI in education serve as a solid foundation for creating training programs aimed at enhancing educators' knowledge and ability to effectively integrate technology into their teaching practices.